Conservation approaches on historic government buildings in Malaysia / Izatul Laili Jabar, Rohaslinda Ramele @ Ramli and Hasnizan Aksah - Jabar, Izatul Laili; Ramele @ Ramli, Rohaslinda; Aksah, Hasnizan (Research Management Institute (RMI), 2011)
The historic building is one that gives us a sense of wonder and makes us want to know more about the people and culture that produced it. It has architectural, aesthetic, history, documentary, archaeological, economic, social and even political and spiritual or symbolic values. The first impact is always emotional, for it is a symbol of our cultural identity and continuity (Feilden B.M; 1994). The historic buildings in Malaysia are unique and valuable assets to this country for their historical values and tourism potential. Historic buildings in Malaysia may possibly classified into six(6) categories, namely shop houses, commercial buildings, religious buildings, private houses, palaces, and institutional buildings (Kuala Lumpur City Council ; 1996).The term conservation has become familiar to almost everybody. People often raise issues of conservation in regard historic buildings. The term of conservation defined as guardianship providing for maintenance, preservation or protection of what presently exists, from being destroyed or changed in an inappropriate manner. It is a process which leads to the prolongation of the life of cultural property and for its utilization now and in the future (Ahmad, A.G; 2008). All elements of historic buildings tend to deteriorate at a lesser or greater rate depending upon various factors such as aging, location and function. Buildings that were built in the early period of British occupation, for instance, often face problems in building materials. Therefore, proper treatment of building repair and maintenance should be given full consideration. The conservation must preserve and if possible enhance the messages and values of cultural property.